(untitled) (Intent Research Scientific Journal, 2023)
In our country, special attention is paid to the development of national values, national spirituality based on a rich cultural heritage, in which the upbringing of the younger generation is one of the urgent tasks of today. Among these tasks, equipping students with knowledge that will enable them to cope with one of the most important challenges of the globalization era - the elimination of environmental threats - is of particular importance.